2014
DOI: 10.1177/0022034514556708
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Basis of Hereditary Enamel Defects in Humans

Abstract: The formation of human enamel is highly regulated at the molecular level and involves thousands of genes. Requisites for development of this highly mineralized tissue include cell differentiation; production of a unique extracellular matrix; processing of the extracellular matrix; altering of cell function during different stages of enamel formation; cell movement and attachment; regulation of ion and protein movement; and regulation of hydration, pH, and other conditions of the microenvironment, to name just … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0
14

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 29 publications
0
80
0
14
Order By: Relevance
“…Moreover, in multiple cases, no mutations have been found in any of these genes, suggesting involvement of other genes in AI 35–38. Recently, Wright et al 39 performed a strategic search in OMIM and found 71 conditions having an enamel phenotype associated with a known molecular aetiology or linked genetic loci. Because of the absence of detailed information, most of the enamel defects reported could not be classified as AI.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in multiple cases, no mutations have been found in any of these genes, suggesting involvement of other genes in AI 35–38. Recently, Wright et al 39 performed a strategic search in OMIM and found 71 conditions having an enamel phenotype associated with a known molecular aetiology or linked genetic loci. Because of the absence of detailed information, most of the enamel defects reported could not be classified as AI.…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent studies revealed that mutations of multiple proteins could cause syndrome-associated and nonsyndromic enamel defects (for review see Refs. [11], but because of the space limitation the present work can discuss only the biomineralization process in general, and the contribution to this by amelogenin, the most abundant enamel protein.…”
Section: Significance Of Intrinsically Disordered Proteins Involved Imentioning
confidence: 99%
“…The genetic control of dental development represents a complex series of events, and occasional mutations in the genes coding enamel proteins may cause alterations that affect the molecular pathways. The consequence is the occurrence of a deficiency in the amount of enamel (hypoplasia), a change in the composition (hypomineralization), or a change in the enamel structure [Wright et al, 2015]. Therefore, amelogenesis is under strict genetic control, and even caries susceptibility can be affected by genetic variation [Simmer and Hu, 2001;Deeley et al, 2008;Vieira et al, 2008;Shimizu et al, 2012].…”
mentioning
confidence: 99%